Recurrent Pneumonia and a Normal Heart: Late Complication after Repair of Hemianomalous Pulmonary Venous Drainage—A Cautionary Tale - Maryanne Caruana; Victor Grech; Jane Somerville (Case Reports in Medicine)
Hemianomalous pulmonary venous drainage with intact atrial septum is a rare congenital anomaly and reports of its surgical repair and the long-term complications related to the correction are only infrequently encountered in the literature. We report the case of a patient with hemianomalous pulmonary venous drainage and intact atrial septum who underwent surgical repair using a pericardial baffle and creation of an “atrial septal defect” aged 15 years. Dyspnoea and recurrent chest infections started 7 months after surgery when he was seen by a respiratory physician without cardiac followup. He presented again aged 28 years with a recurrent pneumonia investigated over 6 weeks and heart pronounced normal from examination and echocardiography. Correct diagnosis was made in Grown Up Congenital Heart (GUCH) clinic stimulating review of data and catheterisation with pulmonary artery angiography which confirmed it. We feel that this case highlights the importance of specialist care and followup for GUCH patients.